(untitled) (Phenomenology, Humanities and Sciences, 2023)
Our ongoing research aims to elucidate the limits and implications of the pure self as a residue of the empirical self in paragraphs 5 and 6 of Husserl’s Fifth Investigation. Therefore, it is necessary to measure the extent to which the second concept of internal consciousness, to which the pure self is linked, does not suffer from a substantial internalism, causing the philosopher to fall into precisely what he so much wishes to refuse, the dualistic metaphysical psychologism. In this sense, we will also see Husserl’s accusation of falling back on the old Cartesian dualism.